Response of Shaver Brown Laying Hens to Different Feeding Space Allowances - Diarra , S.S.; Devi, A. (International Journal of Poultry Science, 2014)
Three hundred 18 week-old Shaver Brown pullets (1,477.40±7.41 g) were allotted to 5 treatment groups containing 3 replicates of 20 pullets each. The treatments consisted of five feeding space allowances (FSA): 5.60, 8.40, 11.20, 14.00 and 16.80 cm/bird. Data were collected on feed consumption, weight change, egg production and feed conversion ratio (feed: dozen eggs) for a period of 20 weeks (18 to 38 weeks of age). All data collected were subjected to analysis of Variance (ANOVA) and significant differences reported at 5% probability. Mean feed consumption, body weight change and egg weight were not significantly affected by FSA. Pullets given access to FSA of 11.20, 14.00 and 16.80 cm/bird laid the first egg at a significantly younger age compared to those given 5.60 and 8.40 cm/bird. Hen-day egg production (HDP) and egg mass increased with increasing FSA up to 14.00 cm/bird. Hen-day production did not differ between the groups given 8.40 and 16.8 cm/bird. Groups given 5.60 cm/bird consumed more feed per dozen egg produced. The lowest feed consumption per dozen eggs was recorded on 11.20 and 14.00 cm FSA per bird. These results suggest that keeping the feeding space between 11.00 and 14.00 cm/hen will improve flock uniformity and reduce cost of egg production of Shaver Brown hens in the study area.